NOTES ON INDONESIAN FRESHWATER ALGAE-I - Arthur M. Scott; Gerald W. Prescott (REINWARDTIA, 1956)
At various times during the last four years Mr.M.Sachlan,of the Laboratory for Inland Fisheries at Bogor, Java, has sent us collections of freshwater algae from the larger islands of the Indonesian Archipelago,-Borneo, Java and Sumatra.To him we express our sincere thanks for his care and effort in obtaining this material,and for affording us the opportunity of studying it.A report on the algae is in course of preparation, and will be published on completion.During our examination we have encountered some curious cases of dichotypy in a species of Staurastrum, involving four different forms, which, if considered separately, might be thought to belong to four different species. They throw a new light upon the relationship between St. wildemani Gutw.and St. subtrifurcatum var. majus West & West, whose similarity has been noted and commented upon by other authors.(Schmidle, 1902, p. 73; Gutwinski, 1902, p. 605; West & West, 1907, p. 215; Krieger, 1933, p. 209; Rich, 1935, p. 151; Fritsch & Rich, 1937, p. 213).